Pengaruh Model Pembelajaran Guided Inquiry dengan Metode Eksperimen Terhadap Keterampilan Proses Siswa - Woro Hastuti, Dyah Ayu; Wiyanto, Wiyanto (UPEJ Unnes Physics Education Journal, 2019)
The purpose of this research to find out the influnce of guided inquiry model with experiment method toward student sciense procsess skil. The method used is posttest only group design. Sample removal used randomly, from X MIPA 4 as experiment class and X MIPA 3 as control class.The research instrument are observation sheets and posttest to evaluated science procsess skill such as 12 characteristics. Observation made while learning activites to evaluate 7 out of 12 characteristics of science procsess skill. The next meeting, posttest made for 1 lesson hour to evalute 5 characteristics of student?s science procsess skill. The result from observation and posttest combined to be tested. Based on calculation, tarithmetic = 8,56 and ttable = 1,66. From this, tarithmetic is bigger than ttable, so the conclusion is guided inquiry learning with experiment method significantly influence to student?s science procsess skill.